A CDA ANALYSIS ON THE SINGAPORE AIRLINES PREMIUM ECONOMY CLASS ADVERTISEMENT: A NOT-SO-WHITE LIE - Siswanta Siswanta; Desca Angelianawati (Universitas Sarjanawiyata Tamansiswa, 2020)
The present study contextualizes critical discourse analysis on Singapore Airlines Premium Economy Class Advertisement to uncover the discrepancies behind their advertisement. Airline Advertisement is intended to attract prospective customers. Singapore Airlines as one of the biggest airline companies in the world is without exception. Singapore Airlines proposes an advertisement which locates their brand as a low-cost airline to attract potential customers in which affordability and comfortability are their selling points. Their advertisement is marketed through glamorous and convincing advertisements as a find a way to attract more passengers. Yet most people do not realize the â€œhiddenâ€ agenda behind those advertisements. Through critical discourse analysis, one can uncover the signs and interrogate the message which lies behind the advertisement. An advertisement is inseparable with their connotation towards certain ideology and meaning behind the â€œcurtainâ€ which manifest through the word choices, images, symbols, and the colors represented there. This paper seeks to unwrap the â€œnot-so-white-lieâ€ represented in Singapore Airlinesâ€™ Premium Economy Class Advertisement through critical discourse analysis and Baudrillardâ€™s four stages of signs.